2016
DOI: 10.1038/srep39718
|View full text |Cite
|
Sign up to set email alerts
|

Eyeblink Synchrony in Multimodal Human-Android Interaction

Abstract: As the result of recent progress in technology of communication robot, robots are becoming an important social partner for humans. Behavioral synchrony is understood as an important factor in establishing good human-robot relationships. In this study, we hypothesized that biasing a human’s attitude toward a robot changes the degree of synchrony between human and robot. We first examined whether eyeblinks were synchronized between a human and an android in face-to-face interaction and found that human listeners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The sharing and transformation of children’s emotional states would emanate from their understanding of the emotional experience that typifies the other ( Giannopulu et al, 2016 , 2018 ; Giannopulu, 2018 ). Based on interpersonal synchronisation, this is the essence of the speaker-listener condition ( Tatsukawa et al, 2016 ). In this context, both interlocutors are performing a scenario of communication trying various verbal and non-verbal emotional reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The sharing and transformation of children’s emotional states would emanate from their understanding of the emotional experience that typifies the other ( Giannopulu et al, 2016 , 2018 ; Giannopulu, 2018 ). Based on interpersonal synchronisation, this is the essence of the speaker-listener condition ( Tatsukawa et al, 2016 ). In this context, both interlocutors are performing a scenario of communication trying various verbal and non-verbal emotional reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also provides suggestions for how we may be able to increase the error rate, that is, by increasing perceived interpersonal closeness and/or establishing behavior synchrony prior to the color perception task. Previous studies have already pointed out that humans display behavior synchrony not only toward other humans (Nakano and Kitazawa, 2010), but also toward an android (Tatsukawa et al, 2016). Furthermore, such studies have shown that adding a modality (e.g., gaze, touch) that biases humans' attitudes toward the android can change the degree of synchrony (Tatsukawa et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have already pointed out that humans display behavior synchrony not only toward other humans (Nakano and Kitazawa, 2010), but also toward an android (Tatsukawa et al, 2016). Furthermore, such studies have shown that adding a modality (e.g., gaze, touch) that biases humans' attitudes toward the android can change the degree of synchrony (Tatsukawa et al, 2016). Thus, if we introduce other modalities prior to the present experiment, we may be able to establish stronger behavior synchrony and, in turn, observe greater congruence with the agents' answers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to visual information, the uses of tactile stimuli in communication devices to contribute the positive experience of users in remote conversation has recently gathered a great deal of attention. From a psychological perspective, it has been suggested that tactile sensations play an important role in building rapport in interpersonal communication ( Gallace and Spence, 2010 ; Tatsukawa et al, 2016 ). Thus, there have been attempts to integrate tactile functions into various media ( Chang et al, 2002 ; Prattichizzo et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%